Hur hantera upprepad korttidsfrånvaro? : Medarbetarnas attityd till Piteå kommuns tidiga rehabiliteringsarbete - Lundberg, Jenny (2012)
Sick leave and its causes have been debated vigorously in the community for many years. The debate has mainly intended long-term illness. This study focuses on short-term absence, which relates to sick leave at maximum 15 days, within the employer's sick pay period. Short term absence is repeated when the employee has been absent on six occasions over 12 months.When opportunities to do something about the living situation is closed (by monitoring facilities have fallen while demands increase) remains for many people only use short-term absence of recovery, or they go into the fatigue . (Theorell, 2003: 9)The study is from the employee’s perspective, and the results show that the employee in the study that has been repeatedly short-term absence considers that the early rehabilitation works in different ways. One of the informants felt aggrieved, and another highlights the problems associated with the rehabilitation of sick leave that can not be traced to her self but to her relatives. The third informant points at working even earlier. This study therefore aimed to follow up Piteå Municipality’s efforts to curb repetitive short term absence. Therefore statistics, which shows how the repeated short-term absence looked out between 2005- 2011 is presented. The empirical data in this study consists of interviews with the personnel manager and rehabilitation consultant, and three employees who have had repeated short term absences. The material has been analyzed through Karasek and Theorell's so-called Requirements-Control-Support model.Piteå Municipality is working with the repeated short-term absence by a working model, which basically involves an initial briefing, individual meeting with rehabilitation consultant and possibly meeting with occupational health services, which in this case is followed by a three part conference where supervisor, the employee and representatives from occupational health services is involved. This aims to ensure that supervisor will get followed up on ideas emerging from the meeting ...